2019
DOI: 10.1073/pnas.1903406116
|View full text |Cite
|
Sign up to set email alerts
|

The optoelectronic microrobot: A versatile toolbox for micromanipulation

Abstract: Microrobotics extends the reach of human-controlled machines to submillimeter dimensions. We introduce a microrobot that relies on optoelectronic tweezers (OET) that is straightforward to manufacture, can take nearly any desirable shape or form, and can be programmed to carry out sophisticated, multiaxis operations. One particularly useful program is a serial combination of “load,” “transport,” and “deliver,” which can be applied to manipulate a wide range of micrometer-dimension payloads. Importantly, microro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
84
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 93 publications
(93 citation statements)
references
References 49 publications
1
84
0
Order By: Relevance
“…In addition, the manipulation and assembly of hybrid metal-polymer microparticles were achieved [62]. It has been further demonstrated that OEK can serve as a versatile and programmable microrobot to perform typical micromanipulations such as "load," "transport," and "deliver" [63]. Firstly, OEK was used to manipulate custom-designed microstructures.…”
Section: Separation and Assembly Of Micro-scaled Particlesmentioning
confidence: 99%
See 2 more Smart Citations
“…In addition, the manipulation and assembly of hybrid metal-polymer microparticles were achieved [62]. It has been further demonstrated that OEK can serve as a versatile and programmable microrobot to perform typical micromanipulations such as "load," "transport," and "deliver" [63]. Firstly, OEK was used to manipulate custom-designed microstructures.…”
Section: Separation and Assembly Of Micro-scaled Particlesmentioning
confidence: 99%
“…This OEK-based microrobot was also validated to be suitable for isolating single cells for clonal expansion and other biomedical applications. It has been further demonstrated that OEK can serve as a versatile and programmable microrobot to perform typical micromanipulations such as "load," "transport," and "deliver" [63]. Firstly, OEK was used to manipulate custom-designed microstructures.…”
Section: Separation and Assembly Of Micro-scaled Particlesmentioning
confidence: 99%
See 1 more Smart Citation
“…Projected micro-pattern provides the system with a flexible electrode that is not available in the predesigned structures used in conventional DEP systems. OET has been widely used in the manipulation of micro-objects [ 25 ] such as cell culture [ 26 , 27 , 28 , 29 ] and microrobot [ 30 , 31 ], and the assembly of sub-millimeter electronic [ 32 , 33 , 34 ] and electrical devices [ 35 , 36 ]. For example, OET is also used to analyze the relative hardness of red blood cells [ 37 ] and conditions that affect the cell membranes of swimming Enterobacter aerogenes bacteria [ 38 ].…”
Section: Introductionmentioning
confidence: 99%
“…Apart from using OT to realize reconfigurable hydrodynamic manipulation via the control of optically driven micro‐motors, optoelectronic tweezer has been developed to combine dielectrophoresis with OT, which is capable of exerting a stronger manipulation force for a given intensity of light for microrobot control. [ 12 ] A shaped particle based on a tapered cylinder fabricated by two‐photon polymerization has been proposed for acting as a passive force clamp, [ 13 ] which facilitates the design of optically trapped objects with specific force profiles. However, the motions of the passive force clamp are mainly for planar translation.…”
Section: Introductionmentioning
confidence: 99%